CONSUMER PROTECTION AGAINST THE RISKS OF ILLEGAL FERRY SERVICES: A CONSUMER PROTECTION LAW PERSPECTIVE (CASE STUDY ON MURSALA ISLAND) - Doni Heri Koeswono; Cahaya Permata (Journal Analytica Islamica, 2026)
Sea transportation to Mursala Island constitutes the primary access supporting marine tourism in Central Tapanuli Regency. However, the operation of small-scale vessels in open waters directly facing the Indian Ocean, combined with weak enforcement of maritime safety regulations, has generated significant legal and safety risks for passengers as consumers. This study examines the legal protection of consumers against risks arising from illegal ferry services to Mursala Island within the framework of Indonesian consumer protection law. Employing an empirical juridical approach, the research integrates statutory, conceptual, and case analyses. Data were collected through field observations, semi-structured interviews with service providers and passengers, and examination of relevant legislation and legal literature. The findings reveal four interrelated categories of risk: geographical and weather-related hazards, technical deficiencies of vessels, absence of proper business licensing, and weak legal protection mechanisms. The study demonstrates that consumer protection remains largely formalistic, as passengers often lack adequate safety facilities, clear safety procedures, transparent information, and enforceable compensation mechanisms. In practice, liability is frequently resolved informally without legal certainty, thereby weakening consumers’ legal position. This research contributes to the discourse on consumer protection in maritime tourism by highlighting the regulatory gap between normative legal frameworks and operational realities in small-scale coastal transport services. Strengthening governmental supervision, enforcing compliance with maritime safety standards, and institutionalizing clear liability mechanisms are imperative to ensure substantive consumer protection.